Cooperation of Hsp70 and Hsp100 chaperone machines in protein disaggregation - Mogk, Axel; Kummer, Eva; Bukau, Bernd (Frontiers in Molecular Biosciences, 2015)
Unicellular and sessile organisms are particularly exposed to environmental stress such as heat shock causing accumulation and aggregation of misfolded protein species. To counteract protein aggregation, bacteria, fungi and plants encode a bi-chaperone system composed of ATP-dependent Hsp70 and hexameric Hsp100 (ClpB/Hsp104) chaperones, which rescue aggregated proteins and provide thermotolerance to cells. The partners act in a hierarchic manner with Hsp70 chaperones coating first the surface of protein aggregates and next recruiting Hsp100 through direct physical interaction. Hsp100 proteins bind to the ATPase domain of Hsp70 via their unique M-domain. This extra domain functions as a molecular toggle allosterically controlling ATPase and threading activities of Hsp100. Interactions between neighboring M-domains and the ATPase ring keep Hsp100 in a repressed state exhibiting low ATP turnover. Breakage of intermolecular M-domain interactions and dissociation of M-domains from the ATPase ring relieves repression and allows for Hsp70 interaction. Hsp70 binding in turn stabilizes Hsp100 in the activated state and primes Hsp100 ATPase domains for high activity upon substrate interaction. Hsp70 thereby couples Hsp100 substrate binding and motor activation. Hsp100 activation presumably relies on increased subunit cooperation leading to high ATP turnover and threading power. This Hsp70-mediated activity control of Hsp100 is crucial for cell viability as permanently activated Hsp100 variants are toxic. Hsp100 activation requires simultaneous binding of multiple Hsp70 partners, restricting high Hsp100 activity to the surface of protein aggregates and ensuring Hsp100 substrate specificity.